Metagenomic insight into the vaginal microbiome in women infected with HPV 16 and 18 - Da-Ryung Jung; Yeseul Choi; Minsoo Jeong; Vineet Singh; Se Young Jeon; Incheol Seo; Nora Jee-Young Park; Yoon Hee Lee; Ji Young Park; Hyung Soo Han; Jae-Ho Shin; Gun Oh Chong (npj Biofilms and Microbiomes)
Abstract Human papillomavirus (HPV) 16 and 18 (HPV 16/18) account for over 70% of cervical cancer (CC) cases, yet their interaction with the vaginal microbiome (VM) remains unclear. This study explored the association between high-risk HPV types (HR-HPVs), VM composition and bacterial function using shotgun metagenomic sequencing. In early-stage cervical lesions, the HPV 16/18 group showed reduced Lactobacillus-dominant community state types compared to other HR-HPVs, while invasive CC exhibited increased pathogenic bacteria, including Streptococcus agalactiae, Fannyhessea vaginae, and Sneathia vaginalis. The VM associated with HPV 16/18 was enriched in immune response and inflammation pathways, whereas other HR-HPVs were linked to cellular metabolism and hormonal signaling. Notably, HPV 16/18 exhibited stronger bacterial-fungal correlations, indicating shifts in the microbial community. Furthermore, 137 metagenome-assembled genomes provided insights into unique microbial genomic signatures. Our study links VM differences with HPV 16/18 oncogenic potential across cervical lesion stages, urging further research for better diagnostics and treatments.